The IRAIT Project Infrared Astronomy from Antarctica - BUSSO, Maurizio Maria; TOSTI, Gino; F. Roncella; M. Bagaglia; G. Nucciarelli; R. Fastellini; O. Straniero; M. Dolci; M. Ragni; I. Di Varano; L. Corcione; C. Abia; et al. (2005)
The Concordia Station (Candidi 2003), on the Antarctica Plateau, will soon become one of the best observatories to perform infrared observations in the 2-20 microm atmospheric windows and beyond, thanks to its low sky background, low temperature and high atmospheric transparency. The possibility of passively cooling the telescope is a further advantage. We describe here the first permanent Antarctic infrared telescope, under development for the Dome C base. It is the International Robotic Antarctic Infrared Telescope (IRAIT). We briefly outline a few scientific motivations for it, then we review the technical characteristics and the status of its development. The infrared camera for IRAIT is described in another dedicated paper in this volume.